Analyzing Grammatical Cohesion in Narrative Text Found in Indonesian EFL Textbook - Khoyrotul Aini, Linda (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2023)
Analyzing textbooks is one way that we know the extent to which the quality of the textbooks that we use in the learning system and also have an important role for the teacher and student learning as a reference and to assist student learning. The researcher conducted this study to find out what grammatical cohesion is and analyze it in narrative text based on the education curriculum. The result of this study revealed that the grammatical cohesion in Indonesia EFL has been widely used in most text. Moreover, the finding showed that reiteration appeared to be the most frequent type of all subcategories of grammatical cohesion. There are 309 grammatical cohesion ties in four narrative texts: references 175 times (56,64%), conjunction 63 times (20,39%), ellipses 41 times (13,27%), and substitution 30 times (9,70%). It can be concluded that the narrative texts analyzed in this research contain several grammatical cohesions and those are compatible as language inputs.